Clinical outcomes in dogs with localized splenic histiocytic sarcoma treated with splenectomy with or without adjuvant chemotherapy. (28th September 2020) - Latifi, Max; Tuohy, Joanne L.; Coutermarsh‐Ott, Sheryl L.; Klahn, Shawna L.; Leeper, Haley; Dervisis, Nikolaos
Abstract: Background: Localized splenic histiocytic sarcoma (HS) in dogs is a poorly understood disease, and could have longer survival times than disseminated or hemophagocytic HS. Understanding the clinical behavior of localized splenic HS can refine treatment recommendations. Objective: To describe the clinical characteristics and outcomes of dogs with localized splenic HS. Animals: Fourteen client‐owned dogs with histologically confirmed splenic HS that received splenectomy. Methods: Multi‐institutional retrospective case series—medical records of dogs with splenic HS were reviewed. Dog signalment, clinicopathologic data, primary and adjuvant treatments, and outcomes were obtained. Survival data were calculated using Kaplan‐Meier analysis. Dog variables such as age, weight, platelet counts were reported using descriptive statistics. The Cox proportional hazards regression method was used to determine whether potential risk factors (weight, age, albumin level, hematocrit, and platelet count) were associated with PFI. Results: Median survival time for the dogs in this study was 427 days. Twelve dogs received adjuvant lomustine‐based chemotherapy. Five dogs (35.7%) were suspected or confirmed to have developed metastatic disease. Eleven dogs died of disease, 1 dog died of unrelated cause, and 2 dogs were alive at final follow‐up. Conclusions and Clinical Significance: Histiocytic sarcoma in dogs can manifest as a localized form in the spleen. Dogs with localized splenic HS treated with surgery ± chemotherapy can experience survival times over a year.